'Viewfinder' mobile learning application for videography and cinematography based on the rules of perspective / Amir Nor Azan Samar ... [et al.] - Samar, Amir Nor Azan; Hamdan, Harim Izzati; Jaapar, Iqbal; Amairudin, Muhammad Firdaus (2021)
Perspective is a way to represent three-dimensional space on a two-dimensional, flat surface. It is one of the fundamentals of art that is very important, to be learned by an artist as a preparation for the new explorations in visual art. As for videography and cinematography, the understanding on linear and atmospheric perspective does play a significant role in producing meaningful results (story build-up, camera shot and composition). Poor understanding on the rules of perspective will lead to poor visualization, that causing less impact in the video. This research aimed to develop a learning aid that will assist in improving the understanding among film, media studies and multimedia course students on the rules of perspective in videography and cinematography. A mobile learning application named 'Viewfinder' with a dedicated lesson plan has been developed through this Design & Development Research (DDR). Data were collected through qualitative approach and analyzed using the six phases thematic analysis by Braun & Clarke (2013). Usability evaluation has been conducted using Mobile Goal Question Metric (mGQM) Model) and results proved that this mobile application is usable to assist and improve user's understanding on linear and atmospheric perspective in videography and cinematography project.